An Empirical Evaluation of Technical, Vocational, Education and Training (Tvet) Processes In Kenya - Ngure, Susan (Advances in Social Sciences Research Journal, 2015)
This paper examines key stakeholders evaluations of the Technical, Vocational, Education and Training (TVET) processes in Kenya. The paper responds to on-going debate in the business community, media and training practitioners to the perceived mismatch of the skills required in the industry and those produced by the TVET program. Data for this paper were collected from government documents, previous research papers, and business reports and editorials. In addition, primary data were collected by using semi-structured questionnaires, focus group discussions and observations. Respondents included education officers, business employers and employee and trainers and trainees of four TVET institutions. Findings: Most stakeholders were happy with TVET objectives and its contribution in furnishing the industry with requisite skills. However, they enumerated various challenges that make it difficult for TVET to respond adequately to the industry’s skill needs. Discussion was guided by the Kirkpatrick’s evaluation model that has four levels: reaction, learning, behaviour and results Recommendations: Addressing the mismatch of skills in TVET institutions: through a current skills’ inventory, tracer studies of TVET graduates, regular program evaluation, creating linkages with the industry, enhancing industrial attachments and a flexible TVET curriculum. Quality of training: Accredit Business owners as trainers, introduce short trainer competency courses and TVET institutions equally. Recognition of prior learning: recognise prior learning methods, create validation mechanisms, integrate of formal and informal trainings and addressing numerous certificates and training levels. Funding TVET: Offer training loans to TVET students, introduce a training levy to businesses Getting value for money. Analyse all training inputs and judge whether the training is worthwhile. Enhancing the status of TVET. Enhance workplace competencies for survival in self-employment and communicate the benefits and successes of TVET training.